Raman Spectroscopy and Applications - Maaz, Khan (IntechOpen, 2017)
Raman spectroscopy has a number of applications in various fields including material science, physics, chemistry, biology, geology, and medicine. This book illustrates necessary insight and guidance in the field of Raman spectroscopy with detailed figures and explanations. This presents deep understanding of new techniques from basic introduction to the advance level for scientists and engineers. The chapters cover all major aspects of Raman spectroscopy and its application in material characterization with special emphasis on both the theoretical and experimental aspects. This book is aimed to provide solid foundation of Raman spectroscopy to the students, scientists, and engineers working in various fields as mentioned above.